Development of a novel system for monitoring strength and conditioning in elite athletes - Gordon, D.; Mullane, S. L.; Conway, P. P.; West, A. A. (Procedia Engineering, 2012)
The aim of the research outlined in this paper was to determine the feasibility of using a network of wireless inertial measurement units (IMUs) to determine velocity-time and power-time relationships in weight training. Inertial navigation system (INS) algorithms have been implemented to account for rotation during a lift. A wireless IMU has been developed by Loughborough University that allows multiple IMUs to be networked using an adapted SimpliciTI protocol. An Olympic barbell has been modified to allow non-invasive attachment of an IMU whilst ensuring bar rotation is captured. Velocity (in the inertial frame) has been determined through integration of accelerometer / gyroscope data allowing calculation of true force and power. Three-dimensional force and 2.5 dimensional video data were simultaneously captured to provide validation for the IMU-determined force and power calculations.